COMFORT IMPROVEMENT USING GARRA RUFA CARE IN OLDER PEOPLE WITH PSORIASIS - AnNaufal, Ahmad; Haryanto, Joni; Makhfudli (International Journal of Psychosocial Rehabilitation, 2020)
Psoriasis decreases the quality of comfort in older people. Over a long period of time, a low level of comfort triggers a risk of psoriasis recurrence. Intervention with GarraRufa Care is an alternative to increase the comfort level of the older people with psoriasis. Aims: This research aims to identify the effect of GarraRufa Care on the comfort of older people with psoriasis and compare it with the older people group that did not undergo GarraRufa Care. Method: A total of 12 older people with psoriasis were chosen as the research respondents. The older people were divided into two groups, namely the treatment group and the control group. This research is a quasi-experiment withtotal sampling technique. The independent variable of this research was the GarraRufa intervention, while the dependent variable was older people’s comfort. The quality of comfort was measured using the Short General Comfort Questionaire (Short GCQ) based on the KatherinKolcaba comfort concept. The results of the study were analyzed using a Mann-Whitney statistical test with p≤0.05. Result: Older people who received GarraRufa Care treatment experienced an increase in the level of comfort (p = 0.027) compared to the control group. However, the treatment and control groups did not have a significant difference (∝= 0,16). Conclusion: GarraRufa Care can reduce psoriasis and improve comfort by providing a "micro massage" effect. In addition, this intervention can reduce the Psoriasis Area and Severity Index (PASI) score, which will have an effect on the older people’s activities.